ASSISTIVE TECHNOLOGY AS SUPPORT FOR THE INCLUSION PROCESS: FROM PUBLIC POLICIES TO LITERATURE - Fachinetti, Tamiris Aparecida [UNESP]; Carbone Carneiro, Relma Urel [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
The Brazilian educational policy ensures the registration of student gives special education in schools, but of these students presents a challenge for professionals at school, use Assistive Technology make it easy the process of inclusion. In this way, this study to intend with one literature review show the importance of Assistive Technology in the process of inclusion. The results show the need for vocational training, financing policies, and effective implementation of this important resource for the inclusion of all.
Keywords: Assistive technology; Inclusion; Student gives special education